Pengaruh Kualitas Layanan, Harga, Lokasi Dan Motivasi Terhadap Kepuasan Konsumen Fitness (Studi Pada Tiara Fitness Center Sunan Drajat Lamongan) - Fauzi, Ahmad Nailul; Wahono, Budi; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Most people think that fitness is only done by young people who want to gain weight. A fitness lifestyle is basically a way of life that involves doing things that make people healthier and fitter. At the Tiara Fitness center Sunan Drajat Lamongan, the average customer is high school and college students, quite a few are adults aged 30 years and over, because in adulthood many of them really care about health and fitness to maintain their body's immunity. The object of this research is the Tiara Fitness center Sunan Drajat Lamongan. The population in this study was 40 (members) fitness consumers. The sampling technique used in this research is a saturated sampling technique so that the sample in this research is 40 (members) fitness consumers. The data analysis method is through multiple linear regression analysis. The research results show that service quality, price, location and motivation simultaneously influence consumer satisfaction at Tiara Fitness Center. Partially, service quality and location have an effect on consumer satisfaction, while price and motivation have no effect on consumer satisfaction. Keyword : Consumer Satisfaction, Service Quality, Price, Location, Motivation.